Cardiologists' and patients' views about the informed consent process and their understanding of the anticipated treatment benefits of coronary angioplasty: A survey study. (March 2020) - Astin, Felicity; Stephenson, John; Probyn, Joy; Holt, Janet; Marshall, Keith; Conway, Dwayne
Background: Percutaneous coronary intervention is a common revascularisation technique. Serious complications are uncommon, but death is one of them. Seeking informed consent in advance of percutaneous coronary intervention is mandatory. Research shows that percutaneous coronary intervention patients have inaccurate perceptions of risks, benefits and alternative treatments. Aim: To assess cardiologists' and patients' views about the informed consent process and anticipated treatment benefits. Methods: Two cross-sectional, anonymous surveys were distributed in England: an electronic version to a sample of cardiologists and a paper-based version to patients recruited from 10 centres. Results: A sample of 118 cardiologists and 326 patients completed the surveys. Cardiologists and patients shared similar views on the purpose of informed consent; however, over 40% of patients and over a third of cardiologists agreed with statements that patients do not understand, or remember, the information given to them. Patients placed less value than cardiologists on the consent process and over 60% agreed that patients depended on their doctor to make the decision for them. Patients' and cardiologists' views on the benefits of percutaneous coronary intervention were significantly different; notably, 60% of patients mistakenly believed that percutaneous coronary intervention was curative. Conclusions: The percutaneous coronary intervention informed consent process requires improvement to ensure that patients are more involved and accurately understand treatment benefits to make an informed decision. Redesign of the patient pathway is recommended to allow protected time for health professionals to engage in discussions using evidence-based approaches such as 'teach back' and decision support which improve patient comprehension.